Perception and evaluation of language identity in East Timorese speakers of Portuguese: language and cognition in a multilingual community - Batoréo, Hanna (2020)
In the present study we propose to focus on perception and evaluation of language attitude and identity in the case of the East Timorese speakers of Portuguese, residing both in Timor-Leste (East Timor - ET) and in Portugal (cf. Batoréo 2005 and following, and the Casadinho corpus, in preparation). Given the richness and the complexity of the linguistic situation observed in ET, its present sociolinguistic situation can be seen as a form of poliglossia, where typologically different languages – belonging to Austronesian, Papuan, and Indo-European families – stay in permanent language contact with each other and play roles of different sociolinguistic varieties. It is claimed that the linguistic identity of ET inhabitants is constructed as a function of their history and the political options taken by their recently independent state with a generation gap observed at 40/50. The data are discussed in light of Cognitive Sociolinguistics (Language and Cognition).